Autentyczny tekst pisany jako pomoc dydak-tyczna w nauczaniu dorosłych komunikowania się w języku specjalistycznym - Markowski, Grzegorz (Neofilolog, 2019)
This paper is an attempt to present the role of authentic written texts in teaching communication in specialist language, based on the example of business language. The terms detailed here include communication, language as communication tool and specialist text. The methods of creating new terms, correlations between the sender of some content and its addressee, and the specialist knowledge held. The options of using specialist texts in business language classes were also presented. In this case such texts include information materials, interviews, certificates, contacts, agreements, statements, confirmations, invoices, orders, reports, other documents and commercial forms and commercial and official correspondence.